Mapping women's empowerment book launch - BRAC Development Institute (BDI) (BRAC University, 2013)
Voice, work and badily integrity glimpses into Pathways of Women's Empowerment. Complied by Samia Rahhim, Pathways programme, BDI. Clips cover digital story by Joyonty Rani Sardar, Upazila Vice Chairman, Dacope, Khulna.